Development of Training Model to Improve Alumni Capacity in Writing Scientific Papers - Nandi Nandi; Epon Ningrum; Jalu Rafli Ismail (Jurnal Pendidikan Geografi Gea, 2023)
The purpose of this community service activity in general is to help alumni of the Masters and Doctoral Study Program in Geography Education, especially those who are teachers and lecturers in empowering their abilities and skills to be more professional through gathering programs (alumni meetings). In particular, this program aims to: (1) determine the extent of alumni's abilities in writing scientific papers; (2) to train skilled alumni in writing scientific papers; (3) find out the opinions of alumni regarding the benefits of training activities and programs run by the study program. Efforts to overcome the problems stated earlier, alternative solutions to problems that will be pursued are as follows: (1) Conduct initial observations or field orientation regarding problems faced by alumni in writing scientific papers; (2) Conduct training on writing scientific papers; (3) Holding alumni meetings in order to strengthen alumni ties. The ultimate goal in this training activity and alumni gathering is to increase the capacity of the knowledge and skills obtained in the training they will apply both individually and in groups to produce scientific work that can increase teacher professionalism. Apart from that, it strengthens the emotional connection between fellow alumni and plans for follow-up of alumni association activities for the Masters and Doctoral Study Program in Geography Education FPIPS UPI.